The Effect of the Make a Match Learning Model Assisted by Picture Card Media on Students' Self-Efficacy in the Human Respiratory System Material - Feby Firmilia Dewi; Nanda Eska Anugrah Nasution; Chairany Rizka; Mohd Faeez Ilias (Pendidikan Kimia, 2026)
Self-efficacy is a crucial psychological construct in education that significantly impacts students' confidence, motivation, and engagement in learning. However, observations in MAN 2 Kota Probolinggo revealed low self-efficacy among students during biology lessons, mainly because teachercentred instruction failed to foster active participation and confidence. This study aimed to examine the effectiveness of the Make a Match learning model, supported by picture card media, in improving students' self-efficacy in learning the human respiratory system. A quasi-experimental design was employed, involving an experimental group taught with the intervention and a control group taught using conventional models. Pretest and posttest data were analyzed using statistical tests to assess the intervention's impact. The findings indicated that the experimental group showed a significant improvement in self-efficacy, with a mean posttest score of 102.44 compared to 90.67 in the control group (t = -7.897, p < .000). The Make a Match model combined with picture card media effectively fostered mastery experiences, vicarious learning, and social persuasion, aligning with Bandura's Social Learning Theory. This research highlights the importance of interactive, visually engaging teaching strategies for building students' confidence and participation, particularly in challenging biology topics such as the human respiratory system. The study enriches scientific knowledge by demonstrating how structured peer interaction and visual aids can enhance self-efficacy in science education. Nevertheless, the study was confined to a single school and a single biological issue, suggesting that future research should focus on broader settings and long-term implications across multiple scientific areas.